Quercetin Actions on Lipid Profiles in Overweight and Obese Individuals: A Systematic Review and Meta-Analysis - Guo, Wenfang; Gong, Xue; Li, Minhui (Current Pharmaceutical Design, 2019)
Background: The lipid profile is associated with metabolic diseases in overweight and obese individuals. Quercetin treatment is suggested to reduce the risk factors for obesity. Objective: The aim of the literature meta-analysis was to determine the range of doses of quercetin administration on plasma lipid levels in overweight and obese human subjects. Methods: Articles searched on EMBASE, PubMed, Cochrane Library, and Web of Science through March 20, 2019, were reviewed independently using predetermined selection criteria. The Cochrane collaboration’s tool for assessing risk of bias was used to assess the quality of the included trials. Heterogeneity was measured using Cochran's Q test and the I-square (I2) statistic. Data were pooled using a random-effects model and the standardized mean difference (SMD) was considered for measuring the overall effect size. Results: Of 176 articles reviewed, 9 randomized clinical trials were selected based on the inclusion criteria. The pooled results for the effect of quercetin administration on LDL-cholesterol (SMD: -002; 95% CI: -0.15–0.11), HDL-cholesterol (SMD: -0.06; 95% CI: -0.19–0.07), triglycerides (SMD: 0.05; 95% CI: -0.08–0.18), and total cholesterol (SMD: 0.04; 95% CI: -0.09–0.17) were not significantly different from the control group results. Quercetin administration at doses of ≥250 mg/day (SMD: -0.58 ; 95% CI: -0.94–-0.22) and total dose ≥14,000 mg (SMD: -0.58 ; 95% CI: -0.94–-0.22) significantly reduced LDL levels; however, HDL-cholesterol, triglycerides, and total cholesterol levels remained unchanged (p > 0.05). Conclusion: Quercetin administration does not affect plasma lipid levels in overweight and obese individuals. However, it significantly reduces LDL-cholesterol levels at doses of ≥250 mg/day and total dose ≥14000 mg.
Keywords: Quercetin